Active and reactive power sharing in parallel operated inverters - Parlak, Koray Sener; Aydemir, Mehmet Timur; Ozdemir, Mehmet (Ieee, 2006)
Active and reactive power sharing of parallel operating inverters has been investigated in this paper. The power sharing is achieved by adjusting the frequency and voltage amplitude of each unit. Each unit has its own controller and these controllers make sure that the total active and reactive power is shared by each unit in proportion with their rated powers, without any communication between them. A system consisting of two inverters has been simulated in MATLAB-Simulink.
13th IEEE Mediterranean Electrotechnical Conference (MELECON 2006) -- MAY 16-19, 2006 -- Benalmadena, SPAIN